2021
DOI: 10.20960/nh.03147
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic gastrostomy for nutritional support in post-stroke dysphagia

Abstract: Introduction: persistent dysphagia affects 15 % of stroke patients and contributes to malnutrition, aspiration, and death. This study aimed to characterize patients with post-stroke dysphagia who 1 underwent percutaneous endoscopic gastrostomy (PEG), and to assess the impact of PEG feeding on nutritional status and outcome.Methods: an observational and retrospective study using records from patients with post-stroke dysphagia who underwent PEG. Body mass index (BMI), serum albumin, transferrin, and cholesterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Previous studies have reported albumin, lymphocyte count, and total cholesterol as risk factors for death after PEG 8,9,26–29 . Albumin is the most abundant protein in human serum and has been used for decades as an indicator of malnutrition in clinically stable patients 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported albumin, lymphocyte count, and total cholesterol as risk factors for death after PEG 8,9,26–29 . Albumin is the most abundant protein in human serum and has been used for decades as an indicator of malnutrition in clinically stable patients 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported albumin, lymphocyte count, and total cholesterol as risk factors for death after PEG. 8 , 9 , 26 , 27 , 28 , 29 Albumin is the most abundant protein in human serum and has been used for decades as an indicator of malnutrition in clinically stable patients. 30 Several studies have reported that albumin is a good predictor of surgical outcomes 31 , 32 ; however, the relative contributions of malnutrition and advanced disease to hypoalbuminemia was not clear in these studies.…”
Section: Discussionmentioning
confidence: 99%